Circadian cuisine in synchronizing holistic nutrition and biological rhythms - Amna Mughal; Muhammad Usman Khalid; Fatima Armish; Rabeea Jannat; Muhammad Maaz; Ayman Furqan (World Nutrition, 2025)
Chronobiology is an emerging area of research exploring the complex relationship between circadian rhythms and nutrition. This review discusses the interplay of chronobiology and overall nutrition. In simpler terms, the time we eat affects our nutrition and metabolic health. Research validation provides the impact of metabolic processes in maintaining circadian rhythms, considering Chrono nutrition as a preventive and management tool in disease diagnosis. The impact of meal timing on cardiovascular health and diabetic patients focuses on chrono-nutrition, which is meant to provide palliative care for chronic diseases. The review also discusses the cultural and social issues associated with eating patterns, including the novelty of social jetlag, and its nutritional implications. The manuscript confronts the challenges and future directions in chrono-nutrition research, identifying gaps in existing knowledge and the potential for personalization of nutrition. Application of chronobiology in personalized medicine appears to hold a silver lining, In terms of nutritional interventions that can be personalized by chronobiology, thus optimizing health results.